Financial Development in the CIS-7 Countries : Bridging the Great Divide - De Nicolo, Gianni (IMF Working Papers; Working Paper ;, 2003)
This paper documents the great divide in the level of financial development between the Commonwealth of Independent States (CIS) 7 countries and the more advanced economies in transition, in particular those of Central and Eastern Europe and Baltic states. It discusses the roots of financial underdevelopment in the CIS-7 countries by examining the differentials in interest rate spreads between the CIS-7 countries and the transition economies that have achieved faster financial development. The roots of the divide are traced to weaknesses in the institutional infrastructure for financial intermediation, which lead to a combination of low depositor trust in the banking system and high credit risk. High credit risk stems mainly from the poor creditor-rights protection and weak auditing and accounting standards. Financial sector reform strategies that fail to give priority to the resolution of weaknesses in the basic financial infrastructure are unlikely to be successful in letting the CIS-7 countries bridge the great divide.